Analysis of the Application of Extradition Law for Perpetrators of Corruption in Indonesia - Simanihuruk, Logerson; Hakim, Abdul; Jannah, Maya (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The rapid advancement of technology has facilitated international interactions, including travel for business, tourism, and other purposes. However, this ease of movement also enables individuals involved in criminal activities, such as corruption, to evade justice by fleeing abroad. This study aims to analyze the application of extradition law for Indonesian corruption offenders who escape overseas. Utilizing a normative juridical approach, the research collects data from books, journals, legislation, and websites, and analyzes media reports on corruption cases and applicable Indonesian laws. The findings indicate that Indonesia has implemented extradition treaties to address corruption cases, allowing for the arrest and return of offenders hiding in other countries to face trial in Indonesia. Notable cases requiring extradition include Djoko Tjandra, Nazaruddin, and Nunun Nurbaeti. The legal framework for extradition is governed by Law Number 1 of 1979 on Extradition, further detailed by regulations such as the Attorney General's Regulation Number 06 of 2018 and the Minister of Foreign Affairs' Regulation Number 13 of 2020. The study concludes that while extradition treaties are crucial for law enforcement, their effectiveness depends on international cooperation and robust legal frameworks. The implications highlight the need for enhanced extradition processes, stronger international collaboration, and improved legal mechanisms to combat transnational corruption and ensure that offenders are held accountable.